Manajemen Kampanye Public Relations Anti Kekerasan Dan Pelecehan Seksual Dalam Mempertahankan Citra Perusahan PT. Kereta Commuter Indonesia - Bunga Maulida; Lilik Sumarni (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this research was to determine the campaign management of a company in an effort to maintain the company's image. In this research, it examined the management of Public Relations campaigns at PT. Indonesian Commuter Train by carrying out an Anti-Sexual Harassment and Violence campaign. The reason for conducting this research is that in Indonesia cases of sexual harassment are very common, almost every year cases of sexual harassment increase, apart from that, one of the criminal acts that is often worried about by KRL commuter line passengers is sexual harassment. Therefore PT. Kereta Commuter Indonesia is carrying out a Public Relations campaign which aims to raise awareness of KRL users regarding the issue of sexual harassment and violence on public transportation. This research uses theories that are relevant to what is being studied, namely campaign management theory (Venus: 2019), as well as corporate image theory (Kotler and Keller: 2013). The method used in this research is descriptive qualitative, the data collection technique used in this research is primary data in the form of interviews with informants and secondary data in the form of documentation, both data and images. With the results of campaign management used by Public Relations PT. Kereta Commuter Indonesia in maintaining the company's image through answers obtained through source triangulation, it was stated that the campaign carried out could educate and minimize sexual harassment and violence within the KR environment and this campaign also had an impact on PT's corporate image. The Indonesian Commuter Train is considered to care about issues related to sexual harassment and violence experienced by KRL users. The inhibiting factor in this anti-sexual harassment and violence campaign is the sexual harassment and violence campaign run by Public Relations PT. The Indonesian Commuter Train has not been fully implemented by KRL users because there are still many cases of harassment that occur in the KRL environment. The supporting factor is that many agencies are participating in this campaign, such as the Loreal brand, they are making talk shows about sexual harassment and violence.